Association and liquid structure of pyridine–acetic acid mixtures determined from neutron scattering using a 'free proton' EPSR simulation model. Issue 10 (11th February 2015) - McCune, Jade A.; Turner, Adam H.; Coleman, Fergal; White, Caithlin M.; Callear, Samantha K.; Youngs, Tristan G. A.; Swadźba-Kwaśny, Małgorzata; Holbrey, John D.
Abstract : Hydrogen-bonded molecular acetic acid chains are observed in acid–base mixtures from small angle neutron diffraction. Abstract : The liquid structure of pyridine–acetic acid mixtures have been investigated using neutron scattering at various mole fractions of acetic acid, χ HOAc = 0.33, 0.50, and 0.67 and compared to the structures of neat pyridine and acetic acid. Data has been modelled using empirical potential structure refinement (EPSR) with a 'free proton' reference model, which has no prejudicial weighting towards either the existence of molecular or ionised species. Analysis of the neutron scattering results shows the existence of hydrogen-bonded acetic acid chains with pyridine inclusions, rather than the formation of an ionic liquid by proton transfer.